Role of licochalcone A in VEGF-induced proliferation of human airway smooth muscle cells: implications for asthma. (2nd January 2017) - Kim, Sung-Ho; Pei, Qing-Mei; Jiang, Ping; Yang, Min; Qian, Xue-Jiao; Liu, Jiang-Bo
Abstract: Asthma is a chronic respiratory disease characterized by reversible airway obstruction with persistent airway inflammation and airway remodeling, which is associated with increased airway smooth muscle (ASM) mass. Licochalcone A is the predominant characteristic chalcone in licorice root. We found that licochalcone A inhibited vascular endothelial growth factor (VEGF)-induced ASM cell proliferation and induced cell cycle arrest. Additionally, VEGF-induced ASM cell proliferation was suppressed via inhibition of extracellular signal-regulated kinase 1/2 (ERK1/2) activity, but not that of Akt. Furthermore, licochalcone A treatment inhibited VEGF-induced activation of VEGF receptor 2 (VEGFR2) and ERK and blocked the downregulation of caveolin-1 in a concentration-dependent manner. Collectively, our findings suggested that licochalcone A inhibited VEGF-induced ASM cell proliferation by suppressing VEGFR2 and ERK1/2 activation and downregulating caveolin-1. Further studies of these mechanisms are needed to facilitate the development of treatments for smooth muscle hyperplasia-associated diseases of the airway, such as asthma.